Pengaruh Terapi Renang Terhadap Perkembangan Motorik Kasar Pada Bayi 0-12 Bulan - awwalul wiladatil qodliyah (Jurnal Keperawatan Muhammadiyah, 2021)
Objective: Children must get the right stimulation in every aspect of their development at an early age. One aspect that must be stimulated is gross motor skills. Children's main aspects of gross motor learning are strength, endurance, speed, agility, balance, reaction time, and coordination. Gross motor movements are body movements that use large muscles involving the activity of the hands, feet and the whole body of children, and these movements control maturity in coordination. One of the activities that can develop children's gross motor skills is swimming. This study aimed to determine the effect of swimming therapy on gross motor development in infants 0-12 months.Methods: This research design is Pre and Post Test with one Group Design. One group is given swimming therapy treatment, which is done a week thrice for four weeks for a duration of 10 minutes. Before the treatment, the infants were pre-tested using the Denver Development Screening Test (DDST), then the post-test was carried out four weeks later. This research was conducted from March – June 2020 and is located at TPMB Sri Wahyuni. The population in this study were all infants aged 0-12 months who were present to do swimming therapy totaling 25 people.Results: Based on the table above, it was found that most of the baby's gender was 16 was girls (64.00%). Most babies aged 5-8 months were 17 people (68.00%) and included in the good nutrition category as many as 15 people (60.00%). This study’s results indicate a decrease in derivatives, which initially, at the pre-test 16 infants included in the Caution category, decreased by two people (10%) to only 14 infants. In the normal category, the data increased by two babies (10%), which can be seen from the pre-test as many as seven babies included in the normal category to as many as 9babies. As for the advanced category, there is no increase or decrease, but the baby becomes more active in moving or responding to the surrounding environment. The results showed a significance value of 0.000 with an alpha of 5%Conclusion: There is an effect of swimming therapy on the development of gross motor skills of infants aged 0-12 months TPMB Sri Wahyuni. The baby's mother needs to pay attention to the baby's needs, including meeting the baby's stimulation needs to support the development of her baby, for example, by swimming and other types of exercise.